The Ephiphytic Ferns on Concervation forest Soemitro Djojohadikusumo PT. Tidar Kerinci Agung (TKA), West Sumatera - Dita, Khairani Harva; Arbain, Ardinis; Mildawati, Mildawati (Metamorfosa: Journal of Biological Sciences, 2018)
Taxonomical study about the ephiphytic ferns on conservation forest Soemitro Djojohadikusumo PT. Tidar Kerinci Agung (TKA) West Sumatera was conducted from May to July 2016 used survey and observation method, and then the samples were processed and identified at Herbarium ANDA, Biology Department. The result of this study have found nine species, six genera family Polypodiaceae of ephiphytic ferns. Each species could be distinguished by some specific morphological characters such as rhizome, frond, stipes, sorus and spora.